Dietary iron and calcium intakes during pregnancy are associated with lower risk of prematurity, stillbirth and neonatal mortality among women in Tanzania. Issue 4 (7th November 2016) - Mosha, Dominic; Liu, Enju; Hertzmark, Ellen; Chan, Grace; Sudfeld, Christopher; Masanja, Honorati; Fawzi, Wafaie
Abstract: Objective: Prematurity, stillbirth and other adverse birth outcomes remain major concerns in resource-limited settings. Poor dietary intake of micronutrients during pregnancy has been associated with increased risk of adverse outcomes. We determined the relationships between dietary Fe and Ca intakes during pregnancy and risks of adverse birth outcomes among HIV-negative women. Design: Women's diet was assessed through repeated 24 h diet recalls in pregnancy. Mean intakes of total Fe, Fe from animal sources and Ca during pregnancy were examined in relation to adverse birth outcomes and neonatal mortality. Women were prescribed daily Fe supplements as per standard perinatal care. Setting: Dar es Salaam, Tanzania. Subjects: A cohort of 7634 pregnant women. Results: Median (interquartile range) daily dietary intake of total Fe, animal Fe and Ca was 11·9 (9·3–14·7), 0·5 (0–1·1) and 383·9 (187·4–741·2) mg, respectively. Total Fe intake was significantly associated with reduced risk of stillbirth (trend over quartiles, P =0·010). Animal Fe intake was significantly associated with reduced risk of preterm birth and extreme preterm birth. Animal Fe intake was inversely related to neonatal mortality risk; compared with women in the lowest intake quartile, those in the top quartile were 0·51 times as likely to have neonatal death (95 % CI 0·33, 0·77). Higher Ca intake was associated with reduced risk of preterm birth (relative risk; 95 % CI: 0·76; 0·65, 0·88) and extreme preterm birth (0·63; 0·47, 0·86). Women in the highest Ca intake quartile had reduced risk of neonatal mortality (0·59; 0·37, 0·92). Conclusions: Daily dietary Fe and Ca intakes among pregnant women are very low. Improvement of women's diet quality during gestation is likely to improve the risks of adverse birth outcomes.